(untitled) (Ustozlar uchun, 2025)
The field of English language teaching has undergone significant transformations over the past decades, aligning itself with the broader trends of educational development that emphasize learner-centered approaches and the integration of innovative techniques. Modern pedagogical methods in English language teaching are characterized by the prioritization of communicative competence, active participation of learners, and the incorporation of various teaching aids and technologies that cater to diverse learning styles and needs. The primary aim of these methods is to foster not only mastery over linguistic competencies such as grammar, vocabulary, listening, speaking, reading, and writing, but also to nurture critical thinking, creativity, collaboration, and cultural awareness among students.